2017
DOI: 10.1017/s0007114517001246
|View full text |Cite
|
Sign up to set email alerts
|

Comparable reductions in hyperpnoea-induced bronchoconstriction and markers of airway inflammation after supplementation with 6·2 and 3·1 g/d of long-chainn-3 PUFA in adults with asthma

Abstract: Although high dose n-3 PUFA supplementation reduces exercise- and hyperpnoea-induced bronchoconstriction (EIB/HIB), there are concurrent issues with cost, compliance and gastrointestinal discomfort. It is thus pertinent to establish the efficacy of lower n-3 PUFA doses. Eight male adults with asthma and HIB and eight controls without asthma were randomly supplemented with two n-3 PUFA doses (6·2 g/d (3·7 g EPA and 2·5 g DHA) and 3·1 g/d (1·8 g EPA and 1·3 g DHA)) and a placebo, each for 21 d followed by 14 d w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 66 publications
1
22
0
4
Order By: Relevance
“…In adults with exercise‐induced bronchoconstriction, multiple studies examining supplementation with n ‐3 LC‐PUFAs showed attenuation of hyperpnoea‐induced bronchoconstriction and/or improved asthma symptoms . However, one study showed no effect in this asthma group .…”
Section: Role Of Fatty Acids In Asthmamentioning
confidence: 99%
“…In adults with exercise‐induced bronchoconstriction, multiple studies examining supplementation with n ‐3 LC‐PUFAs showed attenuation of hyperpnoea‐induced bronchoconstriction and/or improved asthma symptoms . However, one study showed no effect in this asthma group .…”
Section: Role Of Fatty Acids In Asthmamentioning
confidence: 99%
“…Several more recent interventional clinical trials investigated the effects of PUFA supplementation on development and symptoms of asthma. Higher proportions of n-3 PUFAs in the diet are linked with a decreased risk and improved asthma control in both children [201,[220][221][222][223] and adults [47,202,[224][225][226][227][228][229][230][231][232][233][234].…”
Section: Asthmamentioning
confidence: 99%
“…In adulthood, benefits are demonstrated as a decreased prevalence of asthma symptoms, improved asthma control, decreased levels of fractional exhaled nitric oxide (FeNO), blood eosinophilia and improved lung function [47,202,[224][225][226][227][228][229][230][231][232][233][234]. Additionally, n-3 PUFAs have beneficial effects by reducing airway hyperresponsiveness and severity of exercise-induced bronchoconstriction [233].…”
Section: Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…Especially n-3 long-chain PUFA (n-3 LCPUFA) exert well known anti-inflammatory effects, which are in part associated with a change in cell membrane composition (8,9). In line with this concept many studies demonstrated that supplementation of n-3 LCPUFA have beneficial effects on EIA (10)(11)(12)(13)(14)(15). In contrast, there are many studies which failed to show clinical improvement of EIA by n-3 LCPUFA supplementation (16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%